Karapandzic Flap, a Possible Solution to a Case of Advanced Squamous Cell Carcinoma of the Lip - Mendes Abreu, João (2016)
Cutaneous squamous cell carcinoma is a potentially fatal non-melanocytic skin cancer, which results from the uncontrolled proliferation of keratinocytes. Predominant in the head and neck, it’s intimately connected to sun exposed areas. The diagnosis is based on the clinical presentation of the lesion, supported with the assistance of dermoscopy, needing, however, histological confirmation.This paper reports the case of a 71 year old male evaluated for a hyperkeratotic and infiltrative lower lip injury, suggestive of squamous cell carcinoma. After confirming the suspicion we proceeded with the radical excision of the lesion, whose resulting defect occupied 70% of the lower lip length in its middle portion, reaching its total thickness, and immediate reconstruction using Karapandzic’s sliding and rotating flap technique. The end result was characterized by scarring concealed in the physiological grooves and the maintenance of oral continence as well as the sensitivity and lip mobility.